Benthic decapod crustaceans (Crustacea: Decapoda) of Cubagua Island, Venezuela - Hernández-Ávila, Iván; Gómez, Alfredo; Lira, Carlos; Galindo, Lee (Zootaxa, 2007)
The crustacean decapod fauna of Cubagua Island in the Caribbean Sea, Venezuela, an island much affected by coastal upweling, was surveyed. A total of 178 species from 41 families were recorded, of which 56 species were new records for the island; eigth genera and six species were new records for Venezuela. Most species had previously been recorded from the the Caribbean province, 19.7% were endemic for the province, 64.1% had affinities to the Brazilian province, 57.3% to the Texan and Carolinian provinces and 45.5% showed continuous distributions across the provinces but showing less endemism and more affinities with Brazilian province than the general trends of distributions of decapods in the Caribbean. It appears that upwelling processes around the island hinders the development of the typical Caribbean marine ecosystems. The proximity with the northern limit of the Brazilian province also affects the biodiversity of the island.